THE INFLUENCE OF CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE: STUDY ON TWO GOVERNANCE BANKS BASED IN BANDUNG - Sihombing, Jenny; Pangaribuan, Hisar (11th International Scholars Conference, 2016)
Bank is the heart of the nation's economy. Bank Health and its performance should be maintained and enhanced in order to support the stability of the business and the national economy. This study aims to determine whether the implementation of corporate governance, with indicators of transparency, independence, accountability, fairness and responsibility affect the financial performance of the two government-owned banks based in Bandung. The results showed that the implementation of good corporate governance contributed 89% in the determination of the financial performance on two state-owned banks. From the test results also showed that the transparency had a significant effect on financial performance, responsibility had a significant effect on the financial performance and fairness had a significant effect on financial performance. Variable transparancy be the most decisive variable in performance improvement for both state-owned banks, followed by the variable fairness and variable responsibility.